Internal Control System Analysis of Cash Receiving in Medan City Market Regional Companies - Hartati Situmorang (International Journal of Applied Finance and Business Studies, 2022)
The purpose of this study was to determine how the policy implementation of the internal control system in PD. Market and to determine whether the application of the system of internal control over cash receipts in the PD Pasar is implemented properly. Method analyze the data conducted with the descriptive method that is collect the, process and interpretive data obtained so that can give the clear picture hit the accurate ciecumstance and give the boldness for trouble-shooting which is in facing. Writer have conducted the analysis of concerning organization chart, procedure and system of acceptance of cash of at On PD Pasar Kota Medan and get some conclusion that is in principle On PD Pasar Kota Medan have conducted the system of internal control of acceptance of cash of applied according.